Bimbingan Teknis Pemanfaatan Media Digital Di SMPN 2 Kabila - Otoluwa, Yulinda; Nggilu, Nurain; Husain, Wanda; Parebbo, Mardita Dg.; Mahmud, Aisa; Kueno, Nur Fadila; Didipu, Herman (Community : Jurnal Pengabdian Pada Masyarakat, 2025)
This community service program aims to improve teachers' digital literacy and pedagogical competence using interactive digital media, namely Blooket, Nearpod, and Educaplay at SMP Negeri 2 Kabila. The main problem identified was teachers' low understanding of how to optimally integrate digital platforms into the learning process. To address this challenge, intensive training was conducted in three stages: planning, implementation, and evaluation. The training focused on feature introduction, hands-on practice, and the application of digital media in learning designs. The quantitative evaluation results showed an average increase in teacher competence of 65% after participating in the training, with the Nearpod platform achieving the highest understanding score of 69%, followed by Blooket and Educaplay each at 60%. The qualitative evaluation also showed an increase in teacher enthusiasm, active participation, and confidence in using digital technology. In conclusion, structured and applicable training has proven effective in encouraging learning transformation in the digital era, while increasing teacher readiness to integrate technology sustainably in the classroom.